Radar plots: A novel modality for displaying disparate data on the efficacy of eluxadoline for the treatment of irritable bowel syndrome with diarrhea. Issue 8 (25th March 2018) - Brenner, D. M.; Dove, L. S.; Andrae, D. A.; Covington, P. S.; Gutman, C.; Chey, W. D.
Abstract: Background: Patients with irritable bowel syndrome with diarrhea (IBS‐D) experience a range of abdominal and bowel symptoms; successful management requires alleviation of this constellation of symptoms. Eluxadoline, a locally active mixed μ‐ and κ‐opioid receptor agonist and δ‐opioid receptor antagonist, is approved for the treatment of IBS‐D in adults based on the results of 2 Phase 3 studies. Radar plots can facilitate comprehensive, visual evaluation of diverse but interrelated efficacy endpoints. Methods: Two double‐blind, placebo‐controlled, Phase 3 trials (IBS‐3001 and IBS‐3002) randomized patients meeting Rome III criteria for IBS‐D to twice‐daily eluxadoline 75 or 100 mg or placebo. Radar plots were prepared showing pooled Weeks 1‐26 response rates for the primary efficacy composite endpoint (simultaneous improvement in abdominal pain and stool consistency), stool consistency, abdominal pain, urgency‐free days, and adequate relief, and change from baseline to Week 26 in IBS‐D global symptom score, abdominal discomfort, abdominal pain, abdominal bloating, and daily number of bowel movements. Key Results: The studies enrolled 2428 patients. Eluxadoline increased Weeks 1‐26 responder proportions vs placebo for the composite endpoint, stool consistency, abdominal pain, urgency‐free days, and adequate relief. Changes from baseline to Week 26 in IBS‐D global symptom score, abdominal discomfort, abdominal pain, abdominal bloating, and number of bowel movements were greater with eluxadoline vs placebo. Conclusions and Inferences: Data presentation in radar plot format facilitates interpretation across multiple domains, demonstrating that eluxadoline treatment led to improvements vs placebo across 13 endpoints representing the range of symptoms experienced by patients with IBS‐D. Abstract : Data presentation in radar plot format can facilitate evaluation of the diverse array of symptoms and outcomes that are relevant to a symptom‐based condition like irritable bowel syndrome with diarrhea (IBS‐D). In 2 Phase 3 trials, eluxadoline treatment improved stool consistency and frequency, abdominal pain, bloating and discomfort, feelings of urgency, global symptom score, and adequate relief. Radar plots provide a visual demonstration of improvements with eluxadoline across 13 endpoints encompassing the diverse constellation of symptoms experienced by patients with IBS‐D.